Genetic correlation analysis between sepsis and hematological traits: Identifying shared genomic regions - Jianmin Zhang; Miao Hou; Zhenjiang Bai; Jian Wang; Jie Huang (PLoS ONE, 2025)
Background Sepsis, dysregulated cascades of inflammatory response to infection, remains a critical clinical condition, leading to morbidity and mortality. Better understanding of the genetic basis underlying sepsis has the potential to better prevent and treat this potentially life-threatening condition. Recent studies have identified genetic variants for sepsis and accumulated evidence for the relevance of hematological traits. However, genetic correlation analysis, testing the hypothesis of shared genetic underpinning of sepsis and hematological traits, as well as identifying shared specific genetic regions, is lacking. Method In this study, we systematically evaluated the extent and statistical significance of global genetic correlation between sepsis and a comprehensive battery of 29 hematological traits, as well as performed local genetic correlation analysis to pinpoint the shared genomic regions. Results Our analyses revealed significant global genetic correlation between sepsis and five red blood cell indices. Local genetic correlation analyses identified 6–21 genomic regions with lengths ranging from 1.4kb to 5.6Mb shared between sepsis and seven hematological traits. Conclusion Our findings improve our general understanding of the shared genetics between sepsis and different categories of blood cell traits, and have the potential to advance personalized medicine for sepsis.